Construction method of H2S slow-release coating on surface of titanium implant
By fixing the BSA nanoparticles loading H2S donor GYY4137 on the surface of the titanium implant, using dopamine as a binder to construct the H2S sustained-release coating, the problem of lack of biological activity on the surface of the titanium implant was solved and the biocompatibility was significantly improved and new osteogenesis capacity extend the service life of the implant.
Patent Information
- Application Number
- CN202411610354.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
The surface of titanium implants is prone to form a dense titanium dioxide bioinert layer, which lacks biological activity, making it difficult to effectively induce new bone formation, resulting in poor integration between the implant and the host bone and short service life.
Using dopamine as the "binder", the BSA nanoparticles carrying H2S donor GYY4137 were fixed to the surface of the titanium implant, and the H2S sustained release coating was constructed, and the titanium surface was modified using the biologically active substances of H2S.
Through the fixation of polydopamine coating, the stability and durability of the H2S sustained-release coating are ensured, the risk of coating falls off is reduced, and the biocompatibility and new osteogenesis capacity of titanium implants are significantly improved, and the implants are extended service life.
Smart Images

Figure CN119455117A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of biomedical metal materials, and in particular to a method for constructing a H2S slow-release coating on the surface of a titanium implant. Background Art
[0002] In my country, there are many cases of hard tissue (such as bones, teeth, etc.) disease defects caused by internal and external factors such as diseases, aging, sports injuries, and traffic accidents every year. Clinically, there is an urgent need to find an excellent biomedical alternative material to repair or replace the damaged hard tissue in the patient's body. Titanium and its alloy materials are widely used in the field of clinical bone repair due to their good mechanical properties and biocompatibility. However, the surface of titanium materials lacks biological activity because it is easy to form a dense titanium dioxide (TiO2) bioinert layer and cannot effectively induce new bone formation. In the early stage of being implanted in the body, titanium implants are only combined with surrounding bone tissue in a mechanical locking manner, and the wound is difficult to heal, which significantly reduces the service life of the implant. Therefore, how to improve the biological activity of the surface of titanium implants to give them the ability to induce new bone formation, thereby effectively enhancing implant-host bone integration, is still a technical problem to be solved.
[0003] In 1989, scientists detected H2S, which has always been regarded as a toxic gas, in rats and human brains, and confirmed that it may have certain physiological effects. Studies in recent years have shown that H2S at physiological concentrations (less than 300 μm) has specific biological effects and is the third gas signal molecule in the body besides CO and NO. Endogenous H2S is mainly produced by the metabolism of sulfur-containing amino acids, and participates in many physiological functions such as brain development, blood pressure regulation, and inflammatory response by freely diffusing outside the cell. More importantly, H2S has the potential to regulate bone homeostasis and has attracted much attention in recent years. Studies have found that H2S can affect bone marrow mesenchymal stem cells (BMSCs) through thiol-modified transient receptor potential (TRP) channel proteins TRPV3, TRPV6, and TRPM4 to maintain their function and bone homeostasis. However, H2S is a gaseous bioactive substance. Even if it can be dissolved in water (the concentration of the saturated solution is about 70.43 mM at 37 °C), it is difficult to achieve its modification on the surface of titanium implants using conventional surface modification methods.
[0004] The construction of sustained-release coatings of bioactive substances is a hot topic in the current research on biological modification of titanium implant surfaces. Initially, researchers mostly used the porous structure and charged properties of the bioactive coatings on the surface of titanium implants to load bioactive substances by physical adsorption or electrostatic action. TiO2 nanotubes are considered to be an ideal drug delivery platform on the surface of titanium materials because of their simple preparation, good reproducibility, and unique honeycomb structure, which can load a variety of bioactive substances. Alkaline heat treatment, plasma implantation, hydrothermal treatment and other technologies can introduce many bioactive metal elements into the surface of titanium implants. Under physiological conditions, these metal elements are released into the solution through diffusion to exert biochemical stimulation on cells. Proteins, growth factors, bioactive small molecules, etc. can be embedded in the layers of self-assembled coatings on the surface of titanium implants, and are released as the coatings degrade under physiological conditions, playing a role in regulating cell behavior. In addition, dopamine, graphene, etc. can also be used as carriers to assist bioactive substances in modifying the surface of titanium implants. A major feature of constructing a sustained-release coating of bioactive substances is that the type and amount of bioactive substances loaded can be flexibly adjusted to meet individual needs, so it is a very promising method for biological modification of titanium implant surfaces. So, is it possible to construct a sustained-release coating of H2S to indirectly achieve H2S modification of the titanium surface? In order to achieve the controlled release of H2S on the surface of titanium, the present invention selects the new water-soluble GYY4137 synthesized by Professor Moore in 2008 as the donor of exogenous H2S, and uses bovine serum albumin (BSA) nanoparticles as the carrier of GYY4137. Dopamine (DA) is selected as the "adhesive" to fix the BSA nanoparticles loaded with H2S donor GYY4137 to the surface of titanium, so as to achieve the modification of the surface of titanium by H2S. The present invention will promote the development of research on excellent modified coatings on the surface of titanium implants, and has important scientific significance and potential application prospects.
[0005] The above information disclosed in this Background section is only for enhancement of understanding of the background of the present disclosure and therefore it may contain information that does not form the prior art that is already known to one of ordinary skill in the art. Summary of the invention
[0006] The purpose of the present invention is to provide a method for constructing a H2S slow-release coating on the surface of a titanium implant to solve the problems in the above-mentioned background technology.
[0007] In order to achieve the above object, the present invention provides the following technical solution: a method for constructing a H2S slow-release coating on the surface of a titanium implant, comprising the following steps: S1, pretreated titanium implant surface; S2, placing the pretreated titanium implant in a mixed solution of a preset pH value, containing a preset concentration of dopamine and a preset concentration and a preset cross-linking degree of BSA nanoparticles carrying H2S donor GYY4137, under a preset temperature condition, and immersing for a preset time; S3, washing the titanium implant obtained after the operation of steps S1-S2 with deionized water for a preset number of times and storing it at a preset temperature.
[0008] As a possible implementation manner, further, in step S1, the surface pretreatment method of the titanium implant is: grinding the surface with sandpaper to remove the oxide layer.
[0009] As a possible implementation manner, further, the condition temperature of step S2 is > 0 °C, and the pH value of the mixed solution in step S2 is 7.0~14.0.
[0010] As a possible implementation manner, further, the concentration of dopamine in step S2 is > 0 mg / mL, and the concentration of BSA nanoparticles loaded with H2S donor GYY4137 in step S2 is > 0 mg / mL.
[0011] As a possible implementation manner, further, in step S2, the degree of cross-linking of the BSA nanoparticles carrying the H2S donor GYY4137 is > 0%.
[0012] As a possible implementation manner, further, the immersion treatment time in step S2 is > 0 h.
[0013] As a possible implementation manner, further, the number of cleaning times in step S3 is > 0 times, and the storage temperature in step S3 is > 0 °C.
[0014] In the above technical solution, the technical effects and advantages provided by the present invention are: The present invention fixes BSA nanoparticles carrying H2S donors on the surface of titanium implants through the self-polymerization behavior of dopamine on the surface of titanium implants. The strong adhesion of the polydopamine coating to the titanium surface ensures the stability, firmness and durability of the H2S sustained-release coating, and it exists stably in the physiological environment of the body, reducing the risk of implant failure caused by coating shedding. In addition, both polydopamine and BSA materials have good biocompatibility and will not induce immune rejection or inflammation, ensuring the safety of the implant. This efficient coating structure design significantly improves the biocompatibility and clinical application effect of titanium implants while ensuring the continuous release of H2S. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.
[0016] Figure 1 Field emission scanning electron microscopy analysis of six different titanium surfaces. In the figure, Ti refers to the pre-treated sample of commercial medical titanium implants, Ti-PDA refers to polydopamine-coated titanium implants, Ti-BSA refers to titanium implants modified with BSA nanoparticles without H2S donor GYY4137, and Ti-(BSA@GYY) 50 Refers to titanium implants modified with BSA nanoparticles with a cross-linking degree of 50% and loaded with H2S donor GYY4137, Ti-(BSA@GYY) 100 Refers to titanium implants modified with BSA nanoparticles loaded with H2S donor GYY4137 with a cross-linking degree of 100%, Ti-(BSA@GYY) 200 Refers to titanium implants modified with BSA nanoparticles loaded with H2S donor GYY4137 and a cross-linking degree of 200%.
[0017] Figure 2 Ti and Ti-(BSA@GYY) 200 Atomic force microscope analysis of two titanium implants. In the figure, (a) shows the surface morphology of the two titanium implants; (b) shows the root mean square roughness (R q ) and arithmetic mean roughness (R a ).
[0018] Figure 3 Water contact angle and ethylene glycol contact angle of six different titanium surfaces.
[0019] Figure 4 is the surface free energy of six different titanium surfaces.
[0020] Figure 5 Ti-(BSA@GYY) 50 、Ti-(BSA@GYY) 100 and Ti-(BSA@GYY) 200 H2S release behavior from three titanium implant surfaces. DETAILED DESCRIPTION
[0021] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the examples set forth herein; rather, these example embodiments are provided so that the description of the present disclosure will be more comprehensive and complete, and the concept of the example embodiments will be fully conveyed to those skilled in the art.
[0022] The present invention provides Figures 1 to 5 The method for constructing a H2S slow-release coating on the surface of a titanium implant shown comprises the following steps: S1, pretreated titanium implant surface; S2, placing the pretreated titanium implant in a mixed solution of a preset pH value, containing a preset concentration of dopamine and a preset concentration and a preset cross-linking degree of BSA nanoparticles carrying H2S donor GYY4137, under a preset temperature condition, and immersing for a preset time; S3, washing the titanium implant obtained after the operation of steps S1-S2 with deionized water for a preset number of times and storing it at a preset temperature.
[0023] Embodiment 1: The surface of the titanium implant is pretreated by grinding the surface with sandpaper to remove the oxide layer. Example 2: A method for constructing a polydopamine-coated titanium implant, comprising the following steps: S1, polish the titanium implant surface with sandpaper to remove the oxide layer; S2, the pretreated titanium implants were placed in a solution containing 2 mg / mL dopamine at a pH of 8.5 at 25 °C and immersed for 6 h; S3, the titanium implant obtained after steps S1-S2 was washed three times with deionized water and stored at 4 °C.
[0024] Example 3: A method for constructing a titanium implant modified with BSA nanoparticles without H2S donor GYY4137, comprising the following steps: S1, polish the titanium implant surface with sandpaper to remove the oxide layer; S2, the pretreated titanium implants were placed in a mixed solution containing 2 mg / mL dopamine and 1 mg / mL BSA nanoparticles without H2S donor GYY4137 at pH 8.5 at 25 °C and immersed for 6 h; S3, the titanium implant obtained after steps S1-S2 was washed three times with deionized water and stored at 4 °C.
[0025] Example 4: A method for constructing a titanium implant modified with BSA nanoparticles carrying H2S donor GYY4137 with a cross-linking degree of 50%, comprising the following steps: S1, polish the titanium implant surface with sandpaper to remove the oxide layer; S2, the pretreated titanium implants were placed in a mixed solution containing 2 mg / mL dopamine and 1 mg / mL BSA nanoparticles with a cross-linking degree of 50% loaded with H2S donor GYY4137 at a pH of 8.5 at 25 °C and immersed for 6 h; S3, the titanium implant obtained after steps S1-S2 was washed three times with deionized water and stored at 4 °C.
[0026] Example 5: A method for constructing a titanium implant modified with BSA nanoparticles carrying H2S donor GYY4137 and having a cross-linking degree of 100%, comprising the following steps: S1, polish the titanium implant surface with sandpaper to remove the oxide layer; S2, the pretreated titanium implants were placed in a mixed solution containing 2 mg / mL dopamine and 1 mg / mL BSA nanoparticles with 100% cross-linking degree and loaded with H2S donor GYY4137 at pH 8.5 at 25 °C and immersed for 6 h; S3, the titanium implant obtained after steps S1-S2 was washed three times with deionized water and stored at 4 °C.
[0027] Example 6: A method for constructing a titanium implant modified with BSA nanoparticles carrying H2S donor GYY4137 and having a cross-linking degree of 200%, comprising the following steps: S1, polish the titanium implant surface with sandpaper to remove the oxide layer; S2, the pretreated titanium implants were placed in a mixed solution containing 2 mg / mL dopamine and 1 mg / mL BSA nanoparticles with a cross-linking degree of 200% loaded with H2S donor GYY4137 at a pH of 8.5 at 25 °C and immersed for 6 h; S3, the titanium implant obtained after steps S1-S2 was washed three times with deionized water and stored at 4 °C.
[0028] Experimental Example 1: The titanium implant surfaces obtained in Examples 1 to 6 were observed using a field emission scanning electron microscope. It was found that the titanium implant surfaces were relatively smooth after sandpaper polishing; the surface morphology of the titanium implants coated with polydopamine was not significantly different from that of the titanium implants after sandpaper polishing; BSA, (BSA@GYY) 50 、(BSA@GYY) 100 , and (BSA@GYY) 200The four types of nanoparticles were successfully fixed to the surface of titanium implants and were evenly distributed. The morphology of the nanoparticles fixed to the surface of titanium implants did not change significantly, and almost no degraded or degrading nanoparticles were observed ( Figure 1 ).
[0029] Experimental Example 2: The surfaces of the titanium implants obtained in Examples 1 and 6 were observed using an atomic force microscope. It was found that the surface of the titanium implant modified with nanoparticles became rougher, and its root mean square roughness (R q ) and arithmetic mean roughness (R a ) were significantly greater than the R q and R a ( Figure 2 ).
[0030] Experimental Example 3: The wettability of the titanium implant surface obtained in Examples 1 to 6 was observed using a contact angle meter. It was found that polydopamine can improve the hydrophilicity of the titanium implant surface to a certain extent, while BSA, (BSA@GYY) 50 、(BSA@GYY) 100 , and (BSA@GYY) 200 The four nanoparticles had no significant effect on the wettability of titanium implant surfaces ( Figure 3 ).
[0031] Experimental Example 4: Based on the contact angle data, the surface free energy of the titanium implants obtained in Examples 1 to 6 was calculated. It can be seen that polydopamine can increase the surface free energy of the titanium implants to a certain extent. BSA, (BSA@GYY) 50 、(BSA@GYY) 100 , and (BSA@GYY) 200 The four nanoparticles had no significant effect on the surface free energy of titanium implants ( Figure 4 ).
[0032] Experimental Example 5: The H2S release behavior (release rate and cumulative release amount) of the titanium implant surface obtained in Examples 4 to 6 under a physiological environment (PBS solution with pH = 7.4) was observed. It can be seen that the cross-linking degree only affects the H2S release rate, but not the cumulative release amount of H2S ( Figure 5 ).
[0033] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.
Claims
1. A method for constructing a H2S slow-release coating on the surface of a titanium implant, characterized in that: The following steps are involved: S1, pretreated titanium implant surface; S2, placing the pretreated titanium implant in a mixed solution of dopamine at a preset concentration and bovine serum albumin (BSA) nanoparticles carrying H2S donor GYY4137 at a preset concentration and a preset cross-linking degree at a preset pH value under a preset temperature condition, and immersing the solution for a preset time; S3, washing the titanium implant obtained after the operation of steps S1-S2 with deionized water for a preset number of times and storing it at a preset temperature.
2. The method for constructing a H2S slow-release coating on the surface of a titanium implant according to claim 1, characterized in that: The surface pretreatment method of the titanium implant in step S1 is: grinding the surface with sandpaper to remove the oxide layer.
3. The method for constructing a H2S slow-release coating on the surface of a titanium implant according to claim 1, characterized in that: The condition temperature of step S2 is > 0 °C, and the pH value of the mixed solution in step S2 is 7.0~14.
0.
4. The method for constructing a H2S slow-release coating on the surface of a titanium implant according to claim 1, characterized in that: The concentration of dopamine in step S2 is > 0 mg / mL, and the concentration of BSA nanoparticles loaded with H2S donor GYY4137 in step S2 is > 0 mg / mL.
5. The method for constructing a H2S slow-release coating on the surface of a titanium implant according to claim 1, characterized in that: The degree of cross-linking of the BSA nanoparticles loaded with H2S donor GYY4137 in step S2 was > 0%.
6. The method for constructing a H2S slow-release coating on the surface of a titanium implant according to claim 1, characterized in that: The soaking treatment time in step S2 is > 0 h.
7. The method for constructing a H2S slow-release coating on the surface of a titanium implant according to claim 1, characterized in that: The number of cleaning times in step S3 is > 0 times, and the storage temperature in step S3 is > 0 °C.
Citation Information
Patent Citations
Orthopaedic implantation instrument with osteogenesis promoting coating on surface and preparation method
CN112402693A
Albumin-loaded zinc sulfide nanoparticles as well as preparation method and application thereof
CN113499448A
Near-infrared light-responsive antibacterial coating and preparation method thereof
CN114010845A
Preparation method and application of composite nano photo-thermal material
CN118370817A
Preparation method and application of albumin-loaded berbamine hydrochloride nano-composite
CN118750466A